PENGALAMAN IBU HAMIL DALAM MENGATASI KELUHAN PADA TRIMESTER I DI KLINIK PRATAMA TRISMALIA - Mendrofa, Diana Graselani; Simatupang, Lenny Lusia (STIKes Mitra Husada Medan, 2024)
Pregnancy is a reproductive process that requires special care to run well. In pregnancy there will be changes both physiologically and psychologically, these changes are mostly due to the influence of hormones, namely increased progesterone and estrogen hormones, the increase in these hormones will cause various physiological and psychological discomforts in pregnant women in the first trimester. The purpose of this study was to determine the experience of pregnant women in dealing with complaints in the first trimester. This study is a Phenomenological study, data collection was carried out by independent interviews. Participants in this study numbered 10 people who were selected using the purposive sampling technique and participants were primigravida pregnant women in the first trimester with a desired pregnancy. The implementation was carried out at the Pratama Trismalia clinic, researchers came to the clinic to make a time contract and interview participants. The interview results were analyzed using the Miles and Huberman method. In this study, there are 4 themes related to the experiences of pregnant women in overcoming complaints in the first trimester, including (1) Overcoming Physical Complaints: Nausea and Vomiting (Emesis Gravidarum) (2) Overcoming Physical Complaints: Easily Tired (3) Overcoming Psychological Complaints: Feeling Anxious (4) Husband's Support in Overcoming Complaints Experienced in the First Trimester. From the results of the study on 10 (ten) participants, the following conclusions were drawn: Most primigravida pregnant women understand the efforts to overcome physical complaints and psychological complaints felt in the first trimester and some pregnant women are still afraid to do activities and consume food, and husband's support is also important for pregnant women in overcoming physical and psychological complaints experienced by pregnant women in the first trimester. Suggestion: Further and in-depth research is carried out on the experiences of pregnant women in overcoming complaints in the first trimester, especially in primigravida pregnant women, both in qualitative and quantitative research.